Wet Chemical Synthesis of AlxGa1−xAs Nanostructures: Investigation of Properties and Growth Mechanisms - Suchikova, Yana; Kovachov, Sergii; Bohdanov, Ihor; Konuhova, Marina; Zhydachevskyy, Yaroslav; Kumarbekov, Kuat; Pankratov, Vladimir; Popov, Anatoli I. (MDPI, 2024)
This study focuses on the wet chemical synthesis of AlxGa1−xAs nanostructures, highlighting how different deposition conditions affect the film morphology and material properties. Electrochemical etching was used to texture GaAs substrates, enhancing mechanical adhesion and chemical bonding. Various deposition regimes, including voltage switching, gradual voltage increase, and pulsed voltage, were applied to explore their impact on the film growth mechanisms. SEM analysis revealed distinct morphologies, EDX confirmed variations in aluminum content, Raman spectroscopy detected structural disorders, and XRD analysis demonstrated peak position shifts. The findings emphasize the versatility and cost-effectiveness of wet electrochemical methods for fabricating high-quality AlxGa1−xAs films with tailored properties, showing potential for optoelectronic devices, high-efficiency solar cells, and other advanced semiconductor applications. © 2024 by the authors. --//-- This is an open-access article Suchikova, Y.; Kovachov, S.; Bohdanov, I.; Konuhova, M.; Zhydachevskyy, Y.; Kumarbekov, K.; Pankratov, V.; Popov, A.I. Wet Chemical Synthesis of AlxGa1−xAs Nanostructures: Investigation of Properties and Growth Mechanisms. Crystals 2024, 14, 633. https://doi.org/10.3390/cryst14070633 published under the CC BY 4.0 licence.
This research was funded by The National Research Fund of Ukraine with the support of the University of Cambridge, Great Britain, grant number 0124U000223 \u201CDesign and Research of Oxide Heterostructures for Portable Solar Cells\u201D. In addition, the research of A.I.P. and Y.S. was partly supported by COST Action CA20129 \u201CMultiscale Irradiation and Chemistry Driven Processes and Related Technologies\u201D (MultIChem)., Y.S. was partly supported by COST Action CA20126 \u201CNetwork for research, innovation and product development on porous semiconductors and oxides\u201D (NETPORE). Furthermore, A.I.P was partly supported by the HORIZON 2020 RISE-RADON Project \u201CIrradiation driven nanofabrication: computational modelling versus experiment\u201D. The Institute of Solid State Physics, University of Latvia at the Center of Excellence, has received funding from the European Union\u2019s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; AlxGa1−xAs; EDX; electrochemical deposition; electrochemical etching; morphology; Raman spectroscopy; SEM; semiconductors; wet chemical synthesis; XRD